Catalytic Process in Producing Green Aromatics through Fast Pyrolysis of Wood of Five Tropical Fast Growing Trees Species - Joko Sulistyo; Toshimitsu Hata; Ganis Lukmandaru; Yunida Syafriani; Sensho Honma (Masyarakat Peneliti Kayu Indonesia, 2021)
The generation of liquid fuels and chemicals is potential through a catalytic fast pyrolysis (CFP) which is a rapid, inexpensive, and promising method utilizing tropical wood biomass as starting material. There is a little known in the potential of wood biomass from tropical fast-growing trees as starting materials for the production of liquid fuel and chemicals. In this study the formation of aromatics by pyrolytic-gas chromatography/mass spectroscopy (Py-GC/MS) is evaluated on the effect of wood species with different characteristics and its cellulose component to the formation of aromatics. Fast pyrolysis of eucalyptus wood characterized with low content of ash and high percentages of hollocellulose and α-cellulose produced much high relative peaks of levoglucosan and small relative peaks of lignin derived products. Meanwhile high content of vollatile matter and high crystallinity of cellulose attributed balsa and jabon woods as feedstock for fast pyrolysis. The catalytic process in fast pyrolysis of eucalyptus decomposed the most of oxygenated compound such as levoglucosan and furfural into aromatics in the presence of ZSM-5. Coke formation on the surface catalyst might lead partly of decomposition of levoglucosan and furfural to form aromatics in the catalytic fast pyrolysis of balsa wood. Cellulose component determined on the formation of benzene, toluene, styrene, p-xylene, indane, indene, and naphthalene in catalytic fast pyrolysis of wood.